Tingkat Adopsi Teknologi True Shallot Seed di Kecamatan Klambu, Kabupaten Grobogan - Pratiwi, Pusdima Rahma; Santoso, Siswanto Imam; Roessali, Wiludjeng (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2018)
The productivity of shallot in GroboganÂ Regency is still low because the use of superior varieties is limited. The deploymentÂ of superior shallot seed technology thatÂ profitable is widely unknown to farmers.Â This research aims to analyze the adoptionÂ rate of true shallot seed (TSS) technologyÂ and the influence of internal and externalÂ factors of onion farmers on the adoptionÂ of TSS technology. The study was conductedÂ in Klambu District, Grobogan Regency fromÂ July to August 2017 by interviewing 100Â farmers who selected using multistage sampling. Data were analyzed using the descriptive method and logistic regression. The results showed that the adoption rate of TSSÂ technology in Klambu District, GroboganÂ Regency was in a high category. FarmerâsÂ age, land tenure status, cosmopolitan rate,Â requency of interaction with extension agent, and institutional support significantly influenced TSS technology adoption.